Origin, diversity, and maturation of human antiviral antibodies analyzed by high-throughput sequencing - Prabakaran, Ponraj; Zhu, Zhongyu; Chen, Weizao; Gong, Rui; Feng, Yang; Streaker, Emily; Dimitrov, Dimiter S. (Frontiers in Microbiology, 2012)
Our understanding of how antibodies are generated and function could help develop effective vaccines and antibody-based therapeutics against viruses such as HIV-1, SARS Coronavirus (CoV), and Hendra and Nipah viruses (henipaviruses). Although broadly neutralizing antibodies (bnAbs) against the HIV-1 were observed in patients, elicitation of such bnAbs remains a major challenge when compared to other viral targets. We previously hypothesized that HIV-1 could have evolved a strategy to evade the immune system due to absent or very weak binding of germline antibodies to the conserved epitopes that may not be sufficient to initiate and/or maintain an effective immune response. To further explore our hypothesis, we used the 454 sequence analysis of a large naïve library of human IgM antibodies which had been used for selecting antibodies against SARS Coronavirus (CoV) receptor-binding domain (RBD), and soluble G proteins (sG) of Hendra and Nipah viruses (henipaviruses). We found that the human IgM repertoires from the 454 sequencing have diverse germline usages, recombination patterns, junction diversity and a lower extent of somatic mutation. In this study, we identified germline intermediates of antibodies specific to HIV-1 and other viruses as observed in normal individuals, and compared their genetic diversity and somatic mutation level along with available structural and functional data. Further computational analysis will provide framework for understanding the underlying genetic and molecular determinants related to maturation pathways of antiviral bnAbs that could be useful for applying novel approaches to the design of effective vaccine immunogens and antibody-based therapeutics.